2001
DOI: 10.1002/sia.1099
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐related investigations to characterize different preparation techniques of Sb‐doped SnO2 powders

Abstract: Antimony-doped tin oxide powders were prepared using different routes and annealing conditions. The influence of preparation on the distribution of antimony in the powders was studied and correlated with the electrical properties of the powders. A model of doped SnO 2 powder that allows the bulk concentration of the doping element to be calculated from the XPS results is proposed. The doping after crystallization of SnO 2 leads to a very strong surface segregation that is proved by x-ray photoelectron spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
1
28
0
3
Order By: Relevance
“…In previous work [17,18,19] the dependence of the surface and bulk concentrations in Sb-, In-, Nb-doped SnO 2 powders on the method of preparation and the annealing conditions was studied. The enrichment of the doping element at the surface was revealed by X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [17,18,19] the dependence of the surface and bulk concentrations in Sb-, In-, Nb-doped SnO 2 powders on the method of preparation and the annealing conditions was studied. The enrichment of the doping element at the surface was revealed by X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is concluded that the earlier described changes of the electrical properties caused by increasing bulk doping are in this case the main reason for changes of the AP. In fact, the calculated [14,15] bulk doping concentrations are increasing despite of the observed segregation in the same way. The changes of the AP, which occur due to the formation of a surface layer, are small in comparison with these bulk influences.…”
Section: Resultsmentioning
confidence: 64%
“…About 70% of the total amount of the dopant In and 50% of Sb remains in the crystal lattice of SnO 2 . The content of Nb in the bulk is still lower [14,15]. Therefore the Nb doped samples have higher resistivity than Sb doped ones.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5). This shift is connected with the change in the oxidation state of antimony, which in depends on doping concentration [15,25,26,27]. For low doping concentrations Sb 5+ is dominant.…”
Section: Methodsmentioning
confidence: 99%